Unmet needs in patients with first-episode schizophrenia: a longitudinal perspective. - Landolt, K; Rössler, W; Burns, T; Ajdacic-Gross, V; Galderisi, S; Libiger, J; Naber, D; Derks, E; Kahn, R; Fleischhacker, W (2012)
BACKGROUND: This study aimed to identify the course of unmet needs by patients with a first episode of schizophrenia and to determine associated variables. METHOD: We investigated baseline assessments in the European First Episode Schizophrenia Trial (EUFEST) and also follow-up interviews at 6 and 12 months. Latent class growth analysis was used to identify patient groups based on individual differences in the development of unmet needs. Multinomial logistic regression determined the predictors of group membership. RESULTS: Four classes were identified. Three differed in their baseline levels of unmet needs whereas the fourth had a marked decrease in such needs. Main predictors of class membership were prognosis and depression at baseline, and the quality of life and psychosocial intervention at follow-up. Depression at follow-up did not vary among classes. CONCLUSIONS: We identified subtypes of patients with different courses of unmet needs. Prognosis of clinical improvement was a better predictor for the decline in unmet needs than was psychopathology. Needs concerning social relationships were particularly persistent in patients who remained high in their unmet needs and who lacked additional psychosocial treatment.